Improvement of Soil Chemichal Properties using Corn Cob Biochar (BTJ) - Vivin Setiani; Ulvi Priastuti; Dwi Pradevi Yuniarta (Universitas Diponegoro, 2021)
Corn waste is a solid waste that is still limited in use. One of the efforts that can be made to increase the use-value of maize waste is to convert it into biochar. Corn cobs are a component of corn that can be processed into biochar and can improve soil quality. This study aims to analyze the ability of corn waste biochar (in terms of chemical content and gas emissions) in improving soil quality. Primary data were collected by measuring C element using gravimetric method, N element using kjeldahl method, P element using oslen method, K (NH4O AC pH 7), pH using potentiometric, and CO2 emissions from biochar. Biochar is made by burning corn cobs at 500 oC without oxygen for 2 hours. Chemical content measurement of corn cob biochar, known as biochar tongkol jagung (BTJ) and soil, was carried out for eight weeks. The chemical elements of the mixture of biochar and soil at week 8 include C-Organic (0.7%), Total N (0.1%), P2O5 (10.6 ppm), K2O (0.28 me), pH (6.19), and CO2 emissions (6.64 mg CO2/day).